Impaired fungicide activity in plants blocked in disease resistance signal transduction. - Molina, A (1998)
Fungicide action is generally assumed to be dependent on an antibiotic effect on a target pathogen, although a role for plant defense mechanisms as mediators of fungicide action has not been excluded. Here, we demonstrate that in Arabidopsis, the innate plant defense mechanism contributes to the effectiveness of fungicides. In NahG and nim1 (for noninducible immunity) Arabidopsis plants, which normally exhibit increased susceptibility to pathogens, the fungicides metalaxyl, fosetyl, and Cu(OH)2 are much less active and fail to control Peronospora parasitica. In contrast, the effectiveness of these fungicides is not altered in Arabidopsis mutants defective in the ethylene or jasmonic acid signal transduction pathways. Application of the systemic acquired resistance activator benzothiadiazole (BTH) in combination with these fungicides results in a synergistic effect on pathogen resistance in wild-type plants and an additive effect in NahG and BTH-unresponsive nim1 plants. Interestingly, BTH treatment normally induces long-lasting pathogen protection; however, in NahG plants, the protection is transient. These observations suggest that BTH treatment can compensate only partially for an impaired signal transduction pathway and support the idea that pathogen defense mechanisms are under positive feedback control. These observations are strikingly reminiscent of the reduced efficacy of antifungal agents in immunocompromised animals.